Unlocking Market Value through Halal Certification: A Strategic Approach for Culinary MSMEs in Bantaragung Village, Indonesia - Triana Apriani; Rahmat Aji Nuryakin; Sofia Maulida; Ramadhani Hamzah; Prillia Haliawan (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in supporting Indonesia’s economic growth, particularly in the culinary sector. As consumer demand for safe, high-quality, and religiously compliant food products continues to increase, halal certification has become an important factor influencing purchasing decisions among Indonesia’s predominantly Muslim population. Beyond regulatory compliance, halal certification serves as a strategic tool for enhancing product value and business competitiveness. This Community Service Program (PKM), entitled “Halal Certification Strategy as a Value-Added Driver for Culinary MSME Products in Bantaragung Village, Sindangwangi District, Majalengka Regency, West Java,” was conducted on May 8–9, 2026, in collaboration with the Bantaragung Village Government. The program was organized by lecturers from STEBI Bina Essa Bandung Barat, Tri Bhakti College of Economics, Wibawa Karta Raharja College of Economics, and STIE Bisnis Indonesia. Eleven local culinary MSME representatives participated in the activities. The program employed educational workshops, interactive discussions, consultations, and mentoring sessions focused on halal certification procedures and implementation. The results demonstrated improved participant understanding of the importance of halal certification, application requirements, economic benefits, and strategies for integrating halal certification into business development efforts. Participants also gained greater awareness of halal product assurance standards and their role in maintaining consumer trust. The program concludes that halal certification can effectively increase the added value of culinary MSME products, strengthen market competitiveness, and support sustainable business growth through expanded market access and enhanced consumer confidence.